Habitat-Driven Differences in Fish Assemblages Caught by Traditional Bubu Traps in Kapota Atoll, Wakatobi National Park, Indonesia - Sri Pujiyati; Julia Eka Astarini; Steven Solikin; Baigo Hamuna; Efi Noferya Manafi; Muhammad Musrianton; Firman Rusdin; Safirudin Safirudin (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2026)
Bubu are traditional passive fishing traps made from natural materials such as bamboo and are widely used in coral reef fisheries due to their low impact on benthic habitats. This study examines the diversity and community structure of fish associated with different benthic habitats in Kapota Atoll, Wakatobi National Park, Indonesia. Five bamboo traps (88 × 78 × 32 cm) were deployed at five stations representing four habitat types: coral, sand, coral rubble, and seagrass. To minimize fish avoidance, traps were initially left in place for 48 hours to allow odors from new bamboo to dissipate. After this period, traps were retrieved to collect the catch and then redeployed. Sampling was conducted twice. A total of 92 individuals representing 25 species from 14 families were recorded. Ecological indices indicated moderate diversity (H' = 1.277-2.094), high evenness (E = 0.778-0.921), and low dominance (D = 0.141-0.306). Correspondence analysis explained 64.6% of the species–habitat relationship (Axis 1: 36.02%; Axis 2: 28.58%) and identified three assemblages associated with sand/coral/rubble habitats, shallow seagrass (3 m), and deeper seagrass (8 m). Overall, the results indicate that bubu traps are effective for capturing fish diversity across different benthic habitats and can provide useful ecological information for fisheries management, despite their relatively limited sampling area.